Disease Burden in Patients with Glanzmann’s Thrombasthenia: Perspectives from the Glanzmann’s Thrombasthenia Patient/Caregiver Questionnaire - Duncan A; Kellum A; Peltier S; Cooper DL; Saad H (Journal of Blood Medicine, 2020)
Alexander Duncan,1 Angela Kellum,2 Skye Peltier,3 David L Cooper,4 Hossam Saad4 1Department of Pathology & Laboratory Medicine, Emory University School of Medicine, Atlanta, GA, USA; 2Louisiana Center for Bleeding and Clotting Disorders, Tulane University, New Orleans, LA, USA; 3Center for Bleeding and Clotting Disorders, University of Minnesota Medical Center – Fairview, Minneapolis, MN, USA; 4Novo Nordisk Inc., Plainsboro, NJ, USACorrespondence: Alexander DuncanEmory University School of Medicine, Atlanta, GA, USATel +1 404 712 4637Fax +1 404 712 4632Email aduncan@emory.eduPurpose: Glanzmann’s thrombasthenia (GT) is a rare bleeding disorder caused by a mutation in the αIIbβ 3 integrin essential for optimal platelet function and hemostasis. The aim of this study was to identify the burden of GT on patients and caregivers through better understanding of the management and psychosocial impact of this disorder.Patients and Methods: Participants for this online survey were recruited using a rare disease specialty recruiter from Comprehensive Health Education Services. Data were collected from January 31 through March 12, 2019. The questionnaire was designed to collect information regarding demographics, diagnosis, treatment, and psychosocial impact.Results: Of the 45 respondents (24 patients and 21 caregivers), the majority were female (58%), white (64%), and employed full-time (53%) and had no family history of GT (64%). Many patients reported significant bruising at birth (76%), and the mean age at diagnosis was 2.6 years. About half of the patients experienced 1 bleed per day, and 13% had over 500 bleeds of any severity per year. Most bleeds were skin bruising or mouth bleeds, but patients also reported joint/muscle and gastrointestinal bleeds. Most patients reported receiving a platelet transfusion (82%), and some had developed platelet refractoriness (38%) or antibodies (32%). Common treatments were antifibrinolytics (82%) and recombinant activated factor VII (rFVIIa) (42%), likely due to the presence of antibodies. Many (58%) patients experienced issues with excessive bleeding at school; 38% reported missing school as a result. Female patients struggled to find a gynecologist with knowledge of the management of GT. Most patients were satisfied with the support they receive from their current partner (65%) and their friends (76%).Conclusion: Most patients with GT are diagnosed early. Patients experience considerable psychosocial impact. Patient and physician education concerning treatment alternatives and the support of the GT community are critical.Keywords: bleeding disorder, psychosocial impact, recombinant activated factor VII, platelet transfusion, platelet antibodies